Successful treatment of induced oligometastasis and repeated oligoprogression of advanced lung adenocarcinoma with immunotherapy and radiotherapy. Issue 13 (22nd May 2022) - Lee, Ho Young; Kim, Sung Hyun; Lee, Hong Yeul; Lee, Young‐Min; Han, Ji Yeon; Cho, Heunglae; Lee, Hyun‐Kyung
Abstract: Highly active and durable systemic therapies such as targeted therapy and immunotherapy can convert widespread metastatic disease into oligometastatic status, for which metastasis‐directed local intervention can control and potentially prolong survival. Radiation therapy is an effective therapeutic option for oligometastatic and oligoprogressive disease. Here, we present a case of induced oligometastasis and repeated oligoprogressive lung cancer in which more than 6 years of survival was achieved with a combination of immunotherapy and radiotherapy. Abstract : The time line for the clinical course of the patient from diagnosis to last follow‐up with radiographic images Metastasis‐directed local intervention can control and potentially prolong survival. Radiation therapy is the effective therapeutic option for oligometastatic and oligoprogressive disease. Here we present a case of induced oligometastasis and repeated oligoprogressive lung cancer in which more than 6 years of survival was achieved with a combination of immunotherapy and radiotherapy.